Increasing Competence of Student with Special Needs Use a Decision Support System Application - Martika, Tias; Hermawan, Hermawan (Indonesian Journal of Disability Studies, 2020)
This study aimed to improve student competence in conducting identification and assessment of children with special needs. The subjects of this study were the 4th semester students of FKIP UNS PLB in Orthopedagogic subjects with emotional and behavioural obstacles. There were 35 students in total. The method used in this study was qualitative comparative. The data was collected by filling out the self-evaluation instrument about the students' understanding of identification and assessment material in the pre-test and post-test. The data obtained were then analysed in a qualitative descriptive way. Assessment includes seven aspects, namely (1) understanding of identification, (2) understanding of assessment, (3) differences of identification and assessment, (4) importance of identification and assessment of children with special needs, (5) ways of identifying and assessment, (6) implementation of identification and assessment of children with special needs, (7) identification with the Decision Support System. Based on the results obtained by the data that the seven aspects have an increase in student understanding of identification and assessment, so it can be concluded that there is an increase in student competence in the identification and assessment of children with special needs through the use of the Decision Support System (DSS) application.